How to create Legal Protection for Debt Collateral in MSMEs in Indonesia - Emmi Rahmiwita Nasution (Westscience Press, 2023)
This study examines the legal protection available to debt collateral for Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia that are seeking financing from traditional banks. The study used a mixed methods approach, combining quantitative survey data, regression analysis, and qualitative insights to offer a thorough grasp of the issues and possible solutions. The results show a strong relationship between awareness and the belief in the efficacy of legal protection. Important obstacles included lengthy approval procedures, bureaucratic obstacles, and difficulties with collateralized financing. Policy recommendations for regulatory reform, industry cooperation, and awareness-raising are among the implications. Notwithstanding the cross-sectional design and sample representativeness constraints, this study adds to the development of effective legal protection tactics for MSMEs in Indonesia.